COMPARATIVE ANALYSIS OF RAW MATERIAL INVENTORY PLANNING USING JUST IN TIME (JIT) WITH ECONOMIC ORDER QUANTITY (EOQ) (CASE STUDY IN PT PISMA PUTRA TEKSTIL PEKALONGAN) - Mr Kasmari; Lie Liana (Jurnal Ilmiah Dinamika Teknik, 2011)
To get significant cost savings required for production managers to make improvements in inventory management. One method that is often used is the Economic Order Quantity (EOQ) and Just In Time (JIT). Both methods have advantages and disadvantages of each. The downside of this method Economic Order Quantity (EOC) is the burden of causing storage costs, it is because too many raw materials ordered, while the weakness of the Just In Time (JIT) is the emergence of the booking fee. This method vio companies to frequent message items with a small lot size. With the application of the method Just In Time (JIT) and the Economic Order Quantity (EOQ) for the planning period for 1 months resulting Total Inventory Cost (TIC) for the method Just In Time (JIT) of Rp 2,187,534,448 (calculated 3 types of materials ie raw rayon, cotton and polyester) and Total Inventory Cost (TIC) for the method Economic Order Quantity (EOQ) of Rp 2,187,681,189 (calculated three kinds of raw materials, namely fiber rayon, cotton and polyester). Therefore, when applying the method Just In Time (JIT) Total Inventory Cost savings obtained (TIC) of Rp 1,760,892. The savings occur in storage costs (holding costs) to the quantity of inventory on average (I) is lower.   Keywords: Economic Order Quantity, Just in Time, Total Inventory Cost